Enhanced Surveillance of non-O157 Verotoxin-Producing Escherichia coli in Human Stool Samples from Manitoba - Laura H Thompson; Sandra Giercke; Carole Beaudoin; David Woodward; John L Wylie (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Relatively few enhanced surveillance studies have been undertaken to investigate the extent to which verotoxin-producing non-O157 serotypes of Escherichia coli occur in stool samples received for the detection of verotoxin-producing organisms.